Analisis Hubungan Budaya Kerja, Pemberdayaan SDM, Loyalitas terhadap Kinerja Karyawan pada Kantor Sekretariat Daerah Kota Tebing Tinggi - Vanessa Amanda K. Situmorang; Andre Fitriano; Nasywa Putri Aulia Purba; Caesilia Putri Wahyuni Tindaon; Bambang Sutejo (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
As an administrative component of regional apparatus, the Regional Secretariat Office of Tebing Tinggi City assists the leadership of local government at the province and regency/city levels. The study was carried out at this particular institution since its ideals are meant to provide an example for other agencies and technical institutions to follow. This research used a quantitative approach and surveyed 60 workers. The data was analyzed using multiple linear regression. The partial test does not show that company culture significantly affects workers’ productivity. A significance level of 0.000, which is lower than 0.05, and an F-value of 124.715, which is higher than the essential F-value of 2.76, show that all three independent variables concurrently significantly impact the dependent variable. Conversely, human resource empowerment and loyalty partially have a positive and significant impact on employee performance. The coefficient of determination of 86.3% indicates that this model explains the majority of performance variations. Therefore, institutions are advised to focus on enhancing loyalty and human resource empowerment programs.